Teaching English to young learners with technology integration - I. ȘCHIOPU; A. BÎRZOI (ACROSS)
The use of modern technologies in teaching English to young learners, including innovative strategies, methods, techniques and educational digital online resources, is fully expressed in the didactic process.  These technologies create a favourable platform for reforms and research on the preschool curriculum of teaching English in the new era. In the process of preschool instruction of the English language, modern technologies facilitate the implementation of a person-centred approach to teaching, ensure the differentiation and individualization of learning, taking into account the abilities, level of knowledge, children’s preferences and needs. The use of the educational digital online resources is aligned with student interest in learning the English language through the accumulation and expansion of knowledge and experience.